More Extensive Nodal Dissection Improves Survival for Stages I to III of Colon Cancer: A Population-Based Study - Chen, Steven L. (2006)
OBJECTIVE: To determine whether analyzing more lymph nodes in colon cancer specimens improves survival. SUMMARY BACKGROUND DATA: Increasing the number of lymph nodes analyzed has been reported to correlate with improved survival in patients with node-negative colon cancer. METHODS: The Surveillance, Epidemiology, and End Results database was queried for all patients undergoing resection for histologically confirmed colon cancer between the years 1988 and 2000. Patients were excluded for distant metastases or if an unknown number of nodes was sampled. The number of nodes sampled was categorized into 0, 1 to 7, 8 to 14, and ≥15 nodes. Survival curves constructed using the Kaplan-Meier method were compared using log rank testing. A Cox proportional hazard model was created to adjust for year of diagnosis, age, race, gender, tumor grade, tumor size, TNM stage, and percent of nodes positive for tumor. RESULTS: The median number of lymph nodes sampled for all 82,896 patients was 9. For all stages examined, increasing nodal sampling was associated with improved survival. Multivariate regression demonstrated that patients who had at least 15 nodes sampled as compared with 1 to 7 nodes experienced a 20.6% reduction in mortality independent of other patient and tumor characteristics. CONCLUSIONS: Adequate lymphadenectomy, as measured by analysis of at least 15 lymph nodes, correlates with improved survival, independent of stage, patient demographics, and tumor characteristics. Currently, most procedures do not meet this guideline. Future trials of adjuvant therapy should include extent of lymphadenectomy as a stratification factor.